Synergistic Analgesia of Duloxetine and Celecoxib in the Mouse Formalin Test: A Combination Analysis - Sun, Yong-Hai; Dong, Yu-Lin; Wang, Yu-Tong; Zhao, Guo-Li; Lu, Gui-Jun; Yang, Jing; Wu, Sheng-Xi; Gu, Ze-Xu; Wang, Wen (PLOS ONE, 2013)
Duloxetine, a serotonin and noradrenaline reuptake inhibitor, and celecoxib, a non-steroidal anti-inflammatory drug, are commonly used analgesics for persistent pain, however with moderate gastrointestinal side effects or analgesia tolerance. One promising analgesic strategy is to give a combined prescription, allowing the maximal or equal efficacy with fewer side effects. In the current study, the efficacy and side effects of combined administration of duloxetine and celecoxib were tested in the mouse formalin pain model. The subcutaneous (s.c.) injection of formalin into the left hindpaw induced significant somatic and emotional pain evaluated by the biphasic spontaneous flinching of the injected hindpaw and interphase ultrasonic vocalizations (USVs) during the 1 h after formalin injection, respectively. Pretreatment with intraperitoneal (i.p.) injection of duloxetine or celecoxib at 1 h before formalin injection induced the dose-dependent inhibition on the second but not first phase pain responses. Combined administration of duloxetine and celecoxib showed significant analgesia for the second phase pain responses. Combination analgesia on the first phase was observed only with higher dose combination. A statistical difference between the theoretical and experimental ED50 for the second phase pain responses was observed, which indicated synergistic interaction of the two drugs. Concerning the emotional pain responses revealed with USVs, we assumed that the antinociceptive effects were almost completely derived from duloxetine, since celecoxib was ineffective when administered alone or reduced the dosage of duloxetine when given in combination. Based on the above findings, acute concomitant administration of duloxetine and celecoxib showed synergism on the somatic pain behavior but not emotional pain behaviors.